PCSK9: From Basic Science Discoveries to Clinical Trials - Shapiro, Michael D. (Circ Res, 2018)
Unknown fifteen years ago, proprotein convertase subtilisin/kexin type 9 (PCSK9) is now common parlance amongst scientists and clinicians interested in prevention and treatment of atherosclerotic cardiovascular disease. What makes this story so special is not its recent discovery nor the fact that it uncovered previously unknown biology, but rather that these important scientific insights have been translated into an effective medical therapy in record time. Indeed, the translation of this discovery to novel therapeutic serves as one of the best examples of how genetic insights can be leveraged into intelligent target drug discovery. The PCSK9 saga is unfolding quickly but is far from complete. Here, we review major scientific understandings as they relate to the role of PCSK9 in lipoprotein metabolism and atherosclerotic cardiovascular disease and the impact that therapies designed to inhibit its action are having in the clinical setting.